Evaluation of Microstrain in the Regions Surrounding Morse Taper and External Hexagon Implants - De Melo Moreno, André Luiz [UNESP] (2024)
Objective The aim of this study was to compare the Morse taper (MT) + titanium base (Ti-Base) abutment with the external hexagon (EH) + Ti-Base abutment by using the strain gauge method in the mesial, distal, and apical-buccal areas around these types of implants. Materials and Methods This study investigated two groups, MT and EH, each comprising five polyurethane samples with a dental implant (3.75 × 11.5 mm) in the area of artificial tooth 15. The strain gauges were glued to the mesial, distal, and apical-buccal polyurethane areas of all samples in relation to the implant. Ti-Base nonangled abutments were installed on the implants in each group. Ten identical zirconia crowns were constructed by scanning and milling and were subsequently cemented onto the Ti-base abutments with calcium hydroxide cement. Then, an axial load of 100 N was applied to the occlusal region of the zirconia crowns, and strain gauge measurements were taken. Statistical Analysis Strain gauge data were assessed by a two-way analysis of variance (ANOVA) with implant connection and strain gauge position factors, followed by the Bonferroni test (p < 0.05). Results The MT group showed significantly lower microstrain values in the mesial and apical strain gauges compared to the EH group. Conclusion The MT group exhibited less microstrain in the mesial and apical areas of the polyurethane samples near the implant. Consequently, the MT connection was considered more biomechanically advantageous.